The healing rock: Open-air adolescent psychiatric consultations - Spodenkiewicz, Michel (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2023)
This short narrative describes the challenges of adapting consultation settings to both the needs of adolescents with psychiatric disorders and to the institutional constraints. We show how interior and exterior healing spaces may coexist and thereby enrich each other.